1993
DOI: 10.1002/arch.940230404
|View full text |Cite
|
Sign up to set email alerts
|

Defense mechanisms in insects: Certain integumental proteins and tyrosinase are responsible for nonself‐recognition and immobilization of Escherichia coli in the cuticle of developing Ceratitis capitata

Abstract: A defense mechanism in the cuticle of developing C. capitata was demonstrated using an in vitro system consisting of isolated cuticular tyrosinase from C. capitata, cuticular tyrosinase-free proteins, tyrosine, and E. coli. The simultaneous presence of the above components resulted in the formation of large immobilized E. coli aggregates. By contrast, omission of any of the above components failed to produce such aggregates. In other words, E. coli retained their mobility and viability. The results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…It must be underlined, however, that similar coupling reactions occur not only for cell-mediated defense reactions, but also for humoral defense reactions. Indeed, we have already demonstrated the formation of bacterial aggregates via the same mechanism in the integument of C. capifutu larvae (Marmaras et al, 1993;Charalambidis et al, 1994b).…”
Section: Discussionmentioning
confidence: 68%
“…It must be underlined, however, that similar coupling reactions occur not only for cell-mediated defense reactions, but also for humoral defense reactions. Indeed, we have already demonstrated the formation of bacterial aggregates via the same mechanism in the integument of C. capifutu larvae (Marmaras et al, 1993;Charalambidis et al, 1994b).…”
Section: Discussionmentioning
confidence: 68%
“…However, cecropins as well as several other distinct groups of antibacterial peptides are mainly involved in the humoral reactions in the hemolymph (see below). At the same time we demonstrated that certain integumental proteins from Ceratitis capitata larvae have the ability to recognize and immobilize and/or kill Escherichia coli cells, by a mechanism similar to that described for hemocyte proteins (Marmaras et al, 1993;Charalambidis et al, 1995).…”
Section: Immune Response In Insectsmentioning
confidence: 80%
“…1). There are integumental proteins having the ability to recognize and immobilize E. Cali cells (Marmaras et al, 1993). The white pupa mutant of C. capitata which produces white puparia and lacks the ability to form E. coli aggregates (Charalambidis et al, 1994b1, lends credence to the argument regarding the participation of adduct formation between tyrosine derivatives and specific proteins in the immobilization of bacterial invaders.…”
Section: Defense Reactions Based On Po Activitymentioning
confidence: 93%
“…Abrasions and challenge of the ectodermally derived integument will lead to transcriptional activation of the antimicrobial cecropin gene (Brey et al, 1993). An in vitro study showed that certain cuticular proteins are implicated in non-self-recognition of E. coli through binding to its surface (Marmaras et al, 1993). Cuticle proteins are also expressed by hemocytes; one of the major immune competent cell types in invertebrates (Mun˜oz et al, 2002;Bartholomay et al, 2004).…”
Section: Cuticle Domain Proteinsmentioning
confidence: 99%